An interim safety analysis of hepatocellular carcinoma patients administrating oral vitamin K with or without sorafenib - Jung, Dong-Hwan (Korean J Hepatobiliary Pancreat Surg, 2015)
BACKGROUNDS/AIMS: Vitamin K may plays a role in controlling hepatocellular carcinoma (HCC) cell growth. In this study, we intended to present 5-year experience of 72 patients receiving oral vitamin K with or without sorafenib. Its end-point was to evaluate the safety of combination therapy using sorafenib and vitamin K. METHODS: An interim analysis was performed as a single-arm cross-sectional study, including 72 HCC patients who underwent liver resection or transplantation and administered oral vitamin K2 alone (n=47) or with sorafenib (n=25). RESULTS: In all patients, administration of vitamin K2 analog 45 mg/day did not show any noticeable adverse side-effect during vitamin K therapy of 23.3±10.6 months, except for one patient who experienced skin rash at the third day of vitamin K therapy. In 25 patients receiving sorafenib and vitamin K for 6 months or longer, any noticeable adverse side-effect suspected of vitamin K origin was not identified yet. A small proportion of patients showed unexpectedly favorable anti-tumor effects after use of vitamin K with or without sorafenib. CONCLUSIONS: Because add-on of oral vitamin K did not increase the adverse side-effects of sorafenib, a combination therapy with these two agents appears to be worthy of further clinical trial with an expectation of synergistic therapeutic effects.